Understanding the nexus between migration and food security: Evidence from rural farming households in Osun State, Nigeria - Lateef Olatunbosun Jimoh; Kamila Olaide Akintunde; Ahmed Oluwagbemiga Busari; Afusat Adunni Alabi; Khadijat Olaitan Olanrewaju; Ibrahim Adebowale Yakubu (Sustainable Futures)
Despite being a worldwide phenomenon, systematic reflections on the nexus between migration and food security are surprisingly inadequate in major international discourses. This study therefore provides this reflection gap among rural farming households in Osun State, Nigeria. Using a multistage sampling procedure and propensity score matching technique, 200 households were sampled purposively based on their intensity and dominance in rural-urban and intercontinental emigration. Primary data were sourced using a structured questionnaire. Data were presented using percentages and mean, and analyzed with Monthly Per Capital Food Expenditure (MPCFE), migratory effect, and binary logit models. Results show the sampled households are male-headed dominant (75 %), educated, married, and averaged (49.5) years old. Households experienced an average of 1.08 emigrants, 63 % had a positive migratory effect and an average of (N150, 675.00) remittance inflows in the growing season. Migrant males (77 %) outnumbered females (23 %), averaging 21.47 years old. For migrant households, the average MPCFE recorded was (N92, 345.56) surpassing the food security line (2/3 MPCFE), and resulting in the majority (80.0 %) relatively food-secure. Logistic regression modeling shows that migratory effect, labor loss, and households’ size (1 %) were negatively significant; while farming experience, farm size, and income level (5 %) were the positive significant factors influencing food security among the migrant households. Government should embark on rural urbanization for basic amenities to reduce youths’ rural-urban drifts and formalize remittance inflows to reduce costs. Our study contributes to the international literature by highlighting the role that remittances play in compensating for labor loss and ameliorating food insecurity.